Degradation of 2, 2′, 4, 4′-Tetrabrominated diphenyl ether (BDE-47) via the Fenton reaction driven by the dissimilatory metal-reducing bacterium Shewanella oneidensis MR-1. (November 2020) - Peng, Zhaofeng; Shi, Meimei; Xia, Kemin; Dong, Yiran; Shi, Liang
Abstract: A microbially facilitated approach was developed to degrade 2, 2′, 4, 4′-tetrabrominated diphenyl ether (BDE-47). This approach consisted of biological production of Fe(II) and H2 O2 by the dissimilatory metal-reducing bacterium Shewanella oneidensis MR-1 during the repetitive anoxic/oxic cycles and abiotic production of hydroxyl radical (HO ● ) with the biologically produced Fe(II) and H2 O2 via Fenton reaction. Under the condition tested, BDE-47 did not inhibit the growth of S. oneidensis MR-1. Water soluble Fe(III)-citrate and the solid minerals ferrihydrite [Fe(III)2 O3 0.5H2 O] and goethite [Fe(III)OOH] were tested in this study. Under anoxic condition, the amounts of Fe(II) produced by S. oneidensis MR-1 varied among the Fe(III)s tested, which decreased in the order of Fe(III)-citrate > ferrihydrite > goethite. Under subsequent oxic condition, H2 O2 was produced via O2 reduction by S. oneidensis MR-1. The amounts of H2 O2 detected also varied, which decreased in the order of the reactions with Fe(III)-citrate > goethite > ferrihydrite. S. oneidensis MR-1 maintained its ability to produce Fe(II) and H2 O2 for up to seven anoxic/oxic cycles. At each end of anoxic/oxic cycle, HO ● was detected. The amount of HO ● produced decreased in the order of the reactions with ferrihydrite > goethite > Fe(III)-citrate, which was opposite to that of H2 O2 detected. Compared to the controls without HO ●, the amounts of BDE-47 in the reactions with HO ● decreased. The more HO ● in the reaction, the less amount of BDE-47 detected. Furthermore, no BDE-47 degradation was observed when HO ● was scavenged or ferrihydrite was either omitted or replaced by nitrate. Finally, identification of degradation products, such as hydroxylated BDE-47 and trisBDE, dibromophenol and monobromophenol, suggested that OH-addition and Br-substitution by HO ● were the main mechanisms for degrading BDE-47. Collectively, all these results demonstrated for the first time that the Fenton reaction driven by S. oneidensis MR-1 degraded BDE-47 effectively. Graphical abstract: Image 1 Highlights: BDE-47 is degraded via the Fenton reaction driven by Shewanella oneidensis MR-1. BDE-47 degradation is impacted by the Fe(III)s tested. More BDE-47 is degraded with ferrihydrite than that of goethite. More HO ● is produced with ferrihydrite and goethite than that with Fe(III)-citrate. Abstract : BDE-47 is degraded via the Fenton reaction driven by Shewanella oneiden sis MR-1 and the degradation is impacted by the Fe(III)s tested.